Academic Business Intelligence: Can a Small and Medium-sized University Afford to Build and Deploy it within Limited Resources? - Wahyudi Agustiono (Universitas Airlangga, 2019)
Background: For many years, researches on Business Intelligence (BI) development have been popular in primary industry (trading, telecommunication, and manufacturing). Nevertheless, the academic sector has not been the primary beneficiary. This lack of practices also means there has been limited knowledge relating to the development of BI in the academic sectorObjective: This study presents the development of an Academic Business Intelligence (ABI). Taking an actual ABI development project in a small and medium-sized university in Indonesia context, it specifically sought to understand as to why the university needed an ABI and how it could be developed within the limited resources (funding, IT infrastructure and expertise).Methods: Following the business intelligence development roadmap, this study was able to develop an ABI as an attempt to provide a smart way for generating valuable information from scattered data interactively. It also successfully deployed the newly developed ABI into the existing IT legacy and then run a series of pilot testing involving the intended users.Results: The results showed the acceptance rate was high (87.25%) and suggested that the system found to be usable for conducting students' performance assessment and decision making faster. In short, this study contributes to the growing body of BI development literature by providing empirical evidence on how to successfully develop a BI within the unique context of the academic sector.Conclusion: Considering the findings, this study also draws practical recommendations and highlights a few limitations from which future study could address, especially when developing BI or similar ABI in particular.